Association Between MRI-Based Tibial Slope Measurements and Mucoid Degeneration of the Anterior Cruciate Ligament: A Propensity Score–Matched Case-Control Study. Issue 11 (6th November 2020) - Zikria, Bashir; Johnson, Alex; Hafezi-Nejad, Nima; Siddiqui, Yalda; Kwee, Robert M.; Ahlawat, Shivani; Morelli, John N.; Fayad, Laura M.; Kompel, Andrew J.; Haj-Mirzaian, Arya; Pishgar, Farhad; Demehri, Shadpour
Background: The cause of mucoid degeneration (MD) of the anterior cruciate ligament (ACL), which is commonly observed on magnetic resonance imaging (MRI) of patients with knee pain, has yet to be elucidated. Despite the limited evidence on the relationship between ACL lesions (injury and MD) and tibial morphologic features (ie, posterior tibial slope), the potential association between the presence of ACL MD and medial and lateral tibial slope (MTS and LTS) has not been well-established. Purpose: To investigate whether MTS and LTS measurements are associated with the presence of ACL MD. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Consecutive knee MRI examinations of patients referred by an orthopaedic surgeon for potential internal joint derangements were identified within a 4-year period. The presence of ACL MD and the MTS/LTS values were assessed by independent expert observers in consensus in a blinded fashion. From 413 consecutive knee MRI scans, a sample of 80 knees, including 32 knees with ACL MD (cases) and 48 knees with normal ACL (controls), were selected using propensity score matching method for age, sex, body mass index, and presence of severe medial tibiofemoral compartment cartilage damage. The association between ACL MD and MTS/LTS was evaluated using conditional regression models. Results: Knees with ACL MD had higher values of LTS (mean ± SD, 7.18° ± 3.58°) in comparison with control knees (5.32° ± 3.35°). Conditional regression analysis revealed a significant association between LTS measurements (not MTS) and ACL MD; every 1° increase in LTS was associated with a 17% (95% CI, 1%-35%) higher probability of having ACL MD. Conclusion: Excessive LTS was associated with the presence of ACL MD, independent of participants' age, sex, BMI, and cartilage damage severity.